2008
DOI: 10.1016/j.ijrobp.2007.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Volume Changes on 1.5 Tesla Endorectal MRI During Neoadjuvant Androgen Suppression Therapy for Higher-Risk Prostate Cancer and Recurrence in Men Treated Using Radiation Therapy Results of the Phase II CALGB 9682 Study

Abstract: Purpose-We prospectively determined whether the change in tumor volume (TV) during 2 months of neoadjuvant androgen suppression therapy (nAST) measured using conventional 1.5 Tesla endorectal magnetic resonance imaging (eMRI) was associated with the risk of recurrence after radiation (RT) and 6 months of AST. 1997 and 2001, 180 men with clinical stage T1c-T3cN0M0 adenocarcinoma of the prostate were registered. Fifteen were found to be ineligible and the institutional MR radiologist could not assess the TV in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Researchers in some studies have investigated the use of these techniques for prediction of patients' outcome following radiation therapy (27)(28)(29)31,46 ). The results of these studies have suggested that imaging fi ndings can be used to predict treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers in some studies have investigated the use of these techniques for prediction of patients' outcome following radiation therapy (27)(28)(29)31,46 ). The results of these studies have suggested that imaging fi ndings can be used to predict treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by D'Amico et al ( 84 ) showed that prostate tumor volume changes on 1.5-T endorectal MR images during neoadjuvant androgenincreases the risk of radiation-induced toxicity. The choice of radiation dose that offers the best balance between effi cacy and toxicity remains complex ( 64 ).…”
Section: Review: Mr Imaging Of Treated Prostate Cancermentioning
confidence: 99%
“…PSA measurements following prostate cancer therapy are recommended to be obtained every 3 months for 2 years and then every 6 months for an additional 3 years and annually thereafter as noted in D'Amico et al (2008a). Therefore, PSA recurrence is always modeled in the medical literature as a continuous time to the event as noted in D'Amico et al (2005) and D'Amico et al (2008b).…”
Section: Motivating Datamentioning
confidence: 99%